Journey to the Center of the Cell: Cytoplasmic and Nuclear Actin in Immune Cell Functions - Record, Julien; Saeed, Mezida B.; Venit, Tomas; Percipalle, Piergiorgio; Westerberg, Lisa S. (Frontiers in Cell and Developmental Biology, 2021)
Actin cytoskeletal dynamics drive cellular shape changes, linking numerous cell functions to physiological and pathological cues. Mutations in actin regulators that are differentially expressed or enriched in immune cells cause severe human diseases known as primary immunodeficiencies underscoring the importance of efficienct actin remodeling in immune cell homeostasis. Here we discuss recent findings on how immune cells sense the mechanical properties of their environement. Moreover, while the organization and biochemical regulation of cytoplasmic actin have been extensively studied, nuclear actin reorganization is a rapidly emerging field that has only begun to be explored in immune cells. Based on the critical and multifaceted contributions of cytoplasmic actin in immune cell functionality, nuclear actin regulation is anticipated to have a large impact on our understanding of immune cell development and functionality.